Hepatogomax Improves Serum Albumin and Transaminase Enzyme Activity Levels in Sprague Dawley Rats Liver Cirrhosis - Refani Alycia Kusuma; Etika Ratna Noer; Hery Djagat Purnomo; Adriyan Pramono; Endang Mahati; Choirun Nissa (Faculty of Medicine, Universitas Diponegoro, 2022)
ABSTRACTBackground: Patients with liver cirrhosis had liver cell damage and malnutrition risk. Hepatogomax enteral formula consists of soybean flour and goat’s milk flour which could reduce serum albumin, AST, and ALT levels because it contains BCAA amino acids (valine, leucine, and isoleucine) and MCT.Objective: To examine the effect of Hepatogomax enteral formula based on Soybean flour and goat’s milk flour on serum albumin, AST, and ALT levels in Sprague Dawley rats liver cirrhosis.Methods: The true experimental study – pre-post control group used 24 adult Sprague Dawley rats in 4 groups. Groups K(+), P1, and P2 were induced by Thioacetamide 400 mg/kgBW. The groups of P1 and P2 were given the Hepatogomax enteral formula made from soybean flour and goat’s milk flour at a dose of 4.87 g/200gBW and 14.6 g/200gBW for 28 days. Serum albumin levels were determined using the Bromocresol Green (BCG) method while serum AST and ALT were determined using spectrophotometry. Statistical analysis had used Paired T-Test and Kruskal Wallis test with Mann Whitney follow-up test.Results: Serum albumin, AST, and ALT levels in the P1 and P2 groups had significant differences (p<0.05) against the K(-) and K(+) groups. Enteral formula based on soybean flour and goat’s milk flour could increase serum albumin levels and reduce serum AST and ALT levels of P1 and P2 groups. The most significant improvement in serum albumin, AST, and ALT levels was at dose 14.6 g/200gBW.Conclusion: Hepatogomax enteral formula based on Soybean flour and goat’s milk flour could increase serum albumin and redue AST, and ALT levels Sprague Dawley rats liver cirrhosis.